Proximal Tibia Reconstruction After Bone Tumor Resection: Are Survivorship and Outcomes of Endoprosthetic Replacement and Osteoarticular Allograft Similar?. Issue 3 (March 2017) - Albergo, Jose I.; Gaston, Czar L.; Aponte‐Tinao, Luis A.; Ayerza, Miguel A.; Muscolo, Luis D.; Farfalli, Germán L.; Jeys, Lee M.; Carter, Simon R.; Tillman, Roger M.; Abudu, Adesegun T.; Grimer, Robert J.
Abstract: Background: The proximal tibia is one of the most challenging anatomic sites for extremity reconstructions after bone tumor resection. Because bone tumors are rare and large case series of reconstructions of the proximal tibia are lacking, we undertook this study to compare two major reconstructive approaches at two large sarcoma centers. Questions/purposes: The purpose of this study was to compare groups of patients treated with endoprosthetic replacement or osteoarticular allograft reconstruction for proximal tibia bone tumors in terms of (1) limb salvage reconstruction failures and risk of amputation of the limb; (2) causes of failure; and (3) functional results. Methods: Between 1990 and 2012, two oncologic centers treated 385 patients with proximal tibial resections and reconstruction. During that time, the general indications for those types of reconstruction were proximal tibia malignant tumors or bone destruction with articular surface damage or collapse. Patients who matched the inclusion criteria (age between 15 and 60 years old, diagnosis of a primary bone tumor of the proximal tibia treated with limb salvage surgery and reconstructed with endoprosthetic replacement or osteoarticular allograft) were included for analysis (n = 149). In those groups (endoprosthetic or allograft), of the patients not known to have reached an endpoint (death, reconstructive failure, or limb loss) before 2 years, 85% (88 of 104) and 100% (45 of 45) were available for followup at a minimum of 2 years. A total of 88 patients were included in the endoprosthetic group and 45 patients in the osteoarticular allograft group. Followup was at a mean of 9.5 (SD 6.72) years (range, 2‐24 years) for patients with endoprosthetic reconstructions, and 7.4 (SD 5.94) years for patients treated with allografts (range, 2‐21 years). The following variables were compared: limb salvage reconstruction failure rates, risk of limb amputation, type of failures according to the Henderson et al. classification, and functional results assessed by the Musculoskeletal Tumor Society system. Results: With the numbers available, after competitive risk analysis, the probability of failure for endoprosthetic replacement of the proximal tibia was 18% (95% confidence interval [CI], 10.75‐27.46) at 5 years and 44% (95% CI, 31.67‐55.62) at 10 years and for osteoarticular allograft reconstruction was 27% (95% CI, 14.73‐40.16) at 5 years and 32% (95% CI, 18.65‐46.18) at 10 years. There were no differences in terms of risk of failures at 5 years (p = 0.26) or 10 years (p = 0.20) between the two groups. Fifty‐one of 88 patients (58%) with proximal tibia endoprostheses developed a reconstruction failure with mechanical causes being the most prevalent (32 of 51 patients [63%]). A total of 19 of 45 osteoarticular allograft reconstructions failed (42%) and nine of 19 (47%) of them were caused by early infection. Ten‐year risk of amputation after failure for endoprosthetic reconstruction was 10% (95% CI, 5.13‐18.12) and 11% (95% CI, 4.01‐22.28) for osteoarticular allograft with no difference between the groups (p = 0.91). With the numbers available, there were no differences between the groups in terms of the mean Musculoskeletal Tumor Society score (26.58, SD 2.99, range, 19‐30 versus 27.52, SD 1.91, range, 22‐30; p = 0.13; 95% CI, −2, 3 to 0.32). Mean extension lag was more severe in the endoprosthetic group than the osteoarticular allograft group: 13.56° (SD 18.73; range, 0°‐80°) versus 2.41° (SD 5.76; range, 0°‐30°; p < 0.001; 95% CI, 5.8‐16.4). Conclusions: Reconstruction of the proximal tibia with either endoprosthetic replacement or osteoarticular allograft appears to offer similar reconstruction failures rates. The primary cause of failure for allograft was infection and for endoprosthesis was mechanical complications. We believe that the treating surgeon should have both options available for treatment of patients with malignant or aggressive tumors of the proximal tibia. (S)he might consider an allograft in a younger patient to achieve better extensor mechanism function, whereas in an older patient or one with a poorer prognosis where return to function and ambulation quickly is desired, an endoprosthesis may be advantageous. Level of Evidence: Level III, therapeutic study.